Choice of Myocardial Revascularization Strategy in Elderly Patients with Non-ST Elevation Acute Coronary Syndrome - Sviatoslav A. Kalashnikov; Sergii V. Salo (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To identify the differences in clinical and demographic characteristics of elderly patients with non-ST elevation acute coronary syndrome undergoing percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), and to study the factors influencing in-hospital mortality in these patients.Materials and methods. The study had a retrospective, single-center, observational design. Data from 124 patients aged ≥65 years with a diagnosis of non-ST elevation acute coronary syndrome who underwent revascularization by PCI or CABG were analyzed. Ninety patients (72.6 %) underwent percutaneous coronary intervention (PCI group), and 34 patients (27.4 %) underwent coronary artery bypass grafting (CABG group).Results. The median age in both groups was 72 years. The ratio of men to women in the PCI group was 54 to 36, and in the CABG group, 26 to 7 (p = 0.04). The median length of hospital stay in the PCI group was 6 (4.0–6.0) days, and in the CABG group, 13 (10.0–14.7) days (p < .001). The ratio of clinical diagnoses of myocardial infarction to unstable angina in the PCI group was 35 to 55, and in the CABG group, 6 to 28 (p = 0.03). The mean SYNTAX score in the PCI group was 24.4 ± 12.5 points, and in the CABG group, 36.2 ± 12.7 points (p < .001). Patients in the PCI group were more likely to have acute coronary occlusion (p=0.018) and less likely to have chronic coronary occlusion (p=0.045), LM stem lesions (p=<.001), or aorto-ostial lesions (p=0.006). No significant difference was found between the groups in clinical manifestations, comorbidities, and interventions. Factors associated with a higher risk of in-hospital mortality were age (p = 0.04), length of hospitalization (p = 0.009), diagnosis of myocardial infarction (p < .001), chronic kidney disease (p < .001), previous stroke (p = 0.003), acute coronary artery occlusion (p = 0.021), and history of CABG surgery (p = 0.013).Conclusions: Patients aged 65 years and older with non-ST elevation acute coronary syndrome undergoing PCI and CABG differ in gender, diagnosis, type of hospitalization, and anatomical characteristics of coronary artery disease. When choosing a treatment method according to current recommendations, in-hospital mortality in the PCI and CABG groups did not differ. Increasing age, longer hospitalization duration, diagnosis of myocardial infarction, acute coronary occlusion, chronic renal failure, history of stroke, and previous coronary artery bypass graft surgery are factors associated with higher in-hospital mortality, that should be considered when assessing the risks and benefits and choosing a revascularization strategy.